2018
DOI: 10.1016/j.cellsig.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A cellular threshold for active ERK1/2 levels determines Raf/MEK/ERK-mediated growth arrest versus death responses

Abstract: In addition to its conventional role for cell proliferation and survival, the Raf/MEK/Extracellular signal-regulated kinase (ERK) pathway can also induce growth arrest and death responses, if aberrantly activated. Here, we determined a molecular basis of ERK1/2 signaling that underlies these growth inhibitory physiological outputs. We found that overexpression of ERK1 or ERK2 switches ΔRaf-1:ER-induced growth arrest responses to caspase-dependent apoptotic death responses in different cell types. These death r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Consistent with our observation, other groups showed that overexpression of ectopic ERK1/2 can induce robust cell death responses in a subset of human B-Raf V600E melanoma cells [59,60]. Kinase function of ERK1/2 is crucial for these death effects, as catalytic site-disabled ERK2 mutants cannot induce cell death responses [58]. These phenomena suggest that the magnitude of ERK1/2 catalytic activity should be higher than a certain threshold to trigger cell death, while the availability of their death-specific substrates is also important in determining the cell fate.…”
Section: Intrinsic Properties Of Erk1/2 Affecting the Cell Fate Towarsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with our observation, other groups showed that overexpression of ectopic ERK1/2 can induce robust cell death responses in a subset of human B-Raf V600E melanoma cells [59,60]. Kinase function of ERK1/2 is crucial for these death effects, as catalytic site-disabled ERK2 mutants cannot induce cell death responses [58]. These phenomena suggest that the magnitude of ERK1/2 catalytic activity should be higher than a certain threshold to trigger cell death, while the availability of their death-specific substrates is also important in determining the cell fate.…”
Section: Intrinsic Properties Of Erk1/2 Affecting the Cell Fate Towarsupporting
confidence: 92%
“…Intriguingly, mutations that impair the CD site did not affect the growth arrest responses induced by ERK2-L73P/S151D or the aforementioned death responses induced by wild type ERK2 overexpression (Section 2.3) in Raf/MEK-activated cells [58,74]. In contrast, the FRS (Y261N) mutation markedly attenuated the death responses induced by wild-type ERK2 overexpression in Raf/MEK-activated cells [58], suggesting the significance of FRS in ERK1/2-mediated growth inhibitory signaling; the effects of Y261N could not be evaluated in ERK2-L73P/S151D because Y261N inhibited autophosphorylation of this mutant [74]. The F-site signature "Phe-Xaa-Phe-Pro" is relatively less frequent than the D-site signature and is found only in certain ERK1/2 substrates, including the cell-proliferative transcription factors ELK1, c-Fos, Fra1, and c-Myc, as well as the anti-apoptotic BH3-only protein BimEL [76][77][78].…”
Section: Ectopic Expression Of Autophosphorylating Erk2 Mutant Can Inmentioning
confidence: 93%
See 2 more Smart Citations
“…Cell viability was determined by trypan blue exclusion assay (Invitrogen) or by flow cytometry of cells stained with the fluorescent DNA intercalator TO-PRO 3 (Invitrogen). The colorimetric 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide (MTT, Sigma-Aldrich) assay was performed as previously described 19 . For cell cycle and death analyses, flow cytometry of cells stained with annexin V and propidium iodide (Invitrogen) was performed using the Guava EasyCyte flowcytometry system (MilliporeSigma, Billerica, MA, USA), as previously described 47 .…”
Section: Methodsmentioning
confidence: 99%